ANALISIS PENGARUH BRAND IMAGE DAN PERCEIVED USEFULNESS TERHADAP REPURCHASE DECISION BROWSER MOZILLA FIREFOX DENGAN BRAND ATTITUDE SEBAGAI VARIABEL INTERVENING - Pramanawati, Felyna; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2017)
The problems that occur are a decrease in the number of users of Mozilla Firefox. It is characterized by the number of users of other web browsers are increased each month followed by a decline in the number of users of Mozilla Firefox, this indicates that there is a decrease in the user's decision to use back Mozilla Firefox. This study aimed to analyze the influence of brand image and perceived usefulness to the brand attitude and repurchase the decision Mozilla Firefox. The population used in this study are all users of Mozilla Firefox browser in Semarang. The sampling technique used was purposive sampling. Criteria samples taken is the Mozilla Firefox browser in Semarang who have used more than one month as many as 385 users Mozilla Firefox browser in Semarang. Methods of data collection in this study using questionnaires and interviews. Methods of data analysis using path analysis. Based on this research, brand image and perceived usefulness has a positive influence on brand attitude, brand image and brand attitude has a positive effect on repurchase decision, while perceived usefulness repurchase does not affect the decision. Based on the results Sobel Test note that mediates the effect of brand attitude and brand image perceived usefulness of the repurchase decision.